The effectiveness of video conference meeting in information dissemination within the Bank of the Philippine Island(BPI) Southern Mindanao Area reception analysis - Cabiza, Jennevy V.
For the Bank of Philippine Islands (BPI) to cope with their dispersed branches, videoconferencing is increasingly being examined as viable alternative to face-to-face meeting. This study aims to find out if videoconferencing is an effective medium for information dissemination between the three main branches of BPI (Manila, Cebu, and Davao) and whether the said communication medium I rich enough to disseminate complex information. Media Richness Theory by Daft and Lengel was used to evaluate BPI?s videoconference meetings. According to this theory, for a communication medium to be rich, it should convene with the Media Richness criteria, which are the capacity of the medium to provide rapid feedback, presence of multiple communication cues, language variety, personal focus of the medium. This theory also stated that the richer the communication medium, the richer the transmitted information. The clearer, less ambiguous, and accurate the information will be to the receivers of the message. This research was qualitative in nature. This study used the receptive analysis to know the quality of the information the receivers received using videoconferencing. The subjects of this study are the six managers of BPI southern Mindanao area that were constant participants of videoconferencing meetings. This study would like to find out the participants? perceptions of videoconferencing as a potential virtual collaboration medium for business and organization. The sources of analysis were: the semi-structured interviews with the six managers of BPI Business Corporate Center, some observations the researcher noticed, the criteria of Media Richness Theory, and the factors of an effectively communicated message namely, timeliness, clarity, accuracy, credibility, and relevance. This study has found out that BPI?s videoconference is not that rich because of the limitations of their videoconference facilities and some technical problems that the subjects of this study experienced during videoconference meetings. However, it cannot be labeled as lean or poor because it highly converges with the Media Richness criteria of rapid feedback and language variety. The respondents agreed that the information being cascaded through this medium is effective. It is effective in a sense that the medium and the kind of videoconference meeting that BPI has enable their respondents to ask and clarify points if they find it ambiguous and unclear.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication